2015
DOI: 10.1159/000441097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Hypertension Control after Ischaemic Stroke on the Outcome: A Meta-Analysis

Abstract: Background: Accumulating evidence suggests that high blood pressure (BP) increases the risk of cerebral oedema and haemorrhagic transformation of the ischaemic stroke (IS), and that low BP in acute ischaemic stroke (AIS) is associated with a poor prognosis. The best possible management of hypertension after AIS is still uncertain. Materials and Methods: English databases were searched to identify relevant randomized controlled trials assessing the effects of early BP lowering (started within the first 48 h) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Whether or not high BP is associated with poor outcome after acute ischaemic stroke has been extensively debated with conflicting results. Recently, three meta-analyses have neither supported nor opposed early BP lowering in acute ischaemic stroke with respect to the effect on short or long term morbidity and mortality 19,20,21 . It may instead be BP variability 22,23 and extremes of BP 24,25 that have an influence on poorer outcomes in the acute post-stroke phase.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not high BP is associated with poor outcome after acute ischaemic stroke has been extensively debated with conflicting results. Recently, three meta-analyses have neither supported nor opposed early BP lowering in acute ischaemic stroke with respect to the effect on short or long term morbidity and mortality 19,20,21 . It may instead be BP variability 22,23 and extremes of BP 24,25 that have an influence on poorer outcomes in the acute post-stroke phase.…”
Section: Discussionmentioning
confidence: 99%
“…These trials have mostly been conducted in patients with a mild-to-moderate acute ischemic stroke. Overall, they indicated that BP lowering had a neutral effect on death or dependency [9] .…”
Section: © 2016 S Karger Ag Baselmentioning
confidence: 99%
“…The recent meta-analysis by Liu et al [11] showed that early BP lowering after AIS did not significantly affect the risk of early and long-term death, early and long-term dependency, early and long-term death or dependency, long-term stroke recurrence, long-term myocardial infarction, and long-term vascular events. However, the included studies were limited by the late recruitment (many hours after stroke onset) and smaller BP difference between the active and control arms.…”
mentioning
confidence: 98%